Предмет: Алгебра, автор: smorodinovaviktoria0

1) (x-3)(х2 +3х +9) -х(х-3)(х+3)+ 27, если х=-10;
2) (x+2)(x2-2x+4)-х(х-4)(х+4)-8, если х = -5.

Ответы

Автор ответа: nafanya2014
3

1)

(x-3)(х² +3х +9) -х(х-3)(х+3)+ 27=(x-3)·(x²+3x+9-x·(x+3))+27=

=(x-3)·(x²+3x+9-x²-3x)+27=9·(x-3)+27

если x=-10

9·(-10-3)+27=-117+27=-90

2)

(x+2)(x²-2x+4)-х(х-4)(х+4)-8=(x³+8)-x·(x²-16)=x³+8-x³+16x=16x+8

если x=-5

16x+8=16·(-5)+8=-80+8=-72

Похожие вопросы
Предмет: Українська мова, автор: ksunia1977
Предмет: Математика, автор: Наденька04